The novel interaction mode among centromere sub‐complex CENP‐O/P/U/Q/R. Issue 8 (3rd March 2021) - Cao, Beibei; Zhao, Congcong; Zhang, Yu; Wang, Xiaoyu; Ye, Jingjing; Hu, Liqiao; He, Xiaojing
Abstract: The kinetochore is essential for the accurate segregation of sister chromosome in the eukaryote cell. Among the kinetochore subunits, five proteins CENP‐O/P/U/Q/R form a stable complex, referred to as CENP‐O class, and are required for proper kinetochore function. Although the function and structure of yeast COMA complex (CENP‐O/P/U/Q homologs) have been revealed extensively, the assembly mechanism and detail interactions among human CENP‐O class are significantly different and remain largely unclear. Here, we identified the fragment (residues 241‐360) of CENP‐U and the C‐terminal half of CENP‐Q are essential to form a hetero‐complex and interact with CENP‐O/P sub‐complex in vitro. We for the first time showed that CENP‐R does not directly interact with CENP‐O/P in vitro, but indeed interact with CENP‐U and CENP‐Q. Furthermore, both the N‐ and C‐terminus of CENP‐R are required for the interaction with CENP‐U and CENP‐Q. Our research pinpointed a novel interaction pattern that might shed light on the assembly mechanism of vertebrate CENP‐O class. Abstract : We focused on the interaction pattern among CENP‐O/P/U/Q/R sub‐complex by biochemical methods. We for the first time mapped the direct binding regions between CENP‐U and CENP‐Q, which enable to form a stable hetero‐complex in‐vitro. We confirmed that CENP‐R directly interact with CENP‐U and CENP‐Q, and also excluded the interaction possibility between CENP‐R and CENP‐O/P in‐vitro. We further identified the detailed binding pattern that both N‐ and C‐terminus of CENP‐R are required for the interaction with CENP‐U and CENP‐Q.